2019
DOI: 10.1039/c9ta01167f
|View full text |Cite
|
Sign up to set email alerts
|

Piperidinium-functionalized anion exchange membranes and their application in alkaline fuel cells and water electrolysis

Abstract: A series of piperidinium-functionalized anion exchange membranes have been designed and fabricated for alkaline fuel cells and water electrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(93 citation statements)
references
References 46 publications
1
92
0
Order By: Relevance
“…42 The high stability of the alicyclic QAs has been rationalized by a low ring strain combined with the constrained conformations imposed by the ring structure, which increase the transition state energy of both substitution and elimination reactions. 42 Later studies by us and others on AEMs functionalized with alicyclic cations such as piperidinium 25,26,44 and different spirocyclic QAs 32,37,[45][46][47][48][49][50][51] have conrmed a high alkaline stability. However, the results also indicate that the stability is highly dependent on precisely how the cations are attached to the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The high stability of the alicyclic QAs has been rationalized by a low ring strain combined with the constrained conformations imposed by the ring structure, which increase the transition state energy of both substitution and elimination reactions. 42 Later studies by us and others on AEMs functionalized with alicyclic cations such as piperidinium 25,26,44 and different spirocyclic QAs 32,37,[45][46][47][48][49][50][51] have conrmed a high alkaline stability. However, the results also indicate that the stability is highly dependent on precisely how the cations are attached to the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results also indicate that the stability is highly dependent on precisely how the cations are attached to the polymer backbone. 32,47,49,51 If the alicyclic cations are placed in positions where their ring conformation can be deformed, e.g., in a rigid polymer backbone, there is a tendency for the stability to decrease. 25,32 In the present work we have prepared and studied AEMs based on aryl ether-free uorene-based copolymers tethered with quinuclidinium (Qui) cations placed on exible hexyl spacers.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of NMP head group (Figure A(i)) occurs through nucleophilic substitution reaction (S N 2) via OH − ion attack on the bridging benzylic carbon with an EOB of 31.5 kcal/mol as shown in Figure B. It can be observed that the barrier energies for the detachment of different head groups investigated via nucleophilic attack, are essentially the same, suggesting similar governing degradation mechanism regardless of tethered functionality.…”
Section: Resultsmentioning
confidence: 91%
“…Even though DABCO and ABCO produce β‐carbons (consequently β‐hydrogens) upon reaction with benzylic chloride, Hofmann elimination will not proceed due to the impossibility of attaining the required stereoelectronics . NMP‐functionalised AEMs, on the other hand, can undergo degradation via any or combination of three possible mechanisms, namely, OH − ion attack through nucleophilic substitution, ring‐opening elimination, and ring‐opening substitution …”
Section: Introductionmentioning
confidence: 99%
“…However, the existing AEMs still suffer from some challenges such as the trade-off between dimensional stability and conductivity, and the poor alkaline durability, which delayed the large-scale commercialization of AEMFCs. [8][9][10] To achieve high-performance AEMs, materials such as poly(phenylene oxide), 11 poly(styrene), 12 poly(ionic liquid), 13 poly(ether imide), 14 polyolen, 15 poly(arylene ether ketone) 16 and poly(arylene ether sulfone) 17,18 were modied by incorporating with hydroxide ion exchange groups such as imidazolium, 19 quaternary ammonium, 14,15 guanidinium, 20 pyridinium, 21 morpholinium, 22 piperidinium, 11,23 pyrrolidinium, 18,24 phosphonium 25 and metal ions, 26 etc. Furthermore, the microstructure of the AEMs also plays a key role in membrane's properties.…”
Section: Introductionmentioning
confidence: 99%